A Flexible, Implantable, Bioelectronic Electroporation Device for Targeted Ablation of Seizure Foci in the Mouse Brain - Rita Matta; Zsofia Balogh-Lantos; Zoltan Fekete; Martin Baca; Attila Kaszas; David Moreau; Rodney Philip O’Connor (Sensors)
The primary method of treatment for patients suffering from drug-resistant focal-onset epilepsy is resective surgery, which adversely impacts neurocognitive function. Radio frequency (RF) ablation and laser ablation are the methods with the most promise, achieving seizure-free rates similar to resection but with less negative impact on neurocognitive function. However, there remains a number of concerns and open technical questions about these two methods of thermal ablation, with the primary ones: (1) heating; (2) hemorrhage and bleeding; and (3) poor directionality. Irreversible electroporation (IRE) is a proven method of focal ablation, which circumvents all three of the primary concerns regarding focal RF and laser ablation. Here, we demonstrate the in vivo application of a flexible implant with organic electrodes for focal ablation of epilepsy foci using high-frequency IRE (H-FIRE) in mice. Our results show that local, targeted ablation is possible in the close neighborhood of the electrode, paving the way for the clinical application in the treatment of focal epilepsy.